Страсть как фундаментальная составляющая мотива насильственного преступного поведения - Игнатов, Александр Николаевич; Ігнатов, Олександр Миколайович; Ignatov, Aleksandr (My University, 2013)
In the article the analysis of problem of motivation of violent criminal behaviour is carried out in crime-psychological and the theology scientific discursive zone. As basic unit of analysis of motivational sphere of personality of criminal were the category of passion, examined in the structures of spiritual-psychobiological sphere of personality of accomplishing crime of violence, is chosen. A role and functions of passion are exposed as deep basis of motivation of violent criminal behaviour.
Игнатов А. Н. Страсть как фундаментальная составляющая мотива насильственного преступного поведения / А. Н. Игнатов // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 572-580.
Keywords: мотив; мотивация; страсть; внутренний алгоритм динамики мотивации совершения преступления; насильственное поведение; моивація; пристрасть; внутрішній алгоритм динаміки мотивації вчинення злочину; насильницька поведінка; reason; motivation; passion; internal algorithm of dynamics of motivation of commission of crime; violent behavior